Kinetics of water sorption of damaged bean grains: Thermodynamic properties - Paulo C. Corrêa; Fernanda M. Baptestini; Jaime D. B. Vanegas; Rafael Leite; Fernando M. Botelho; Gabriel H. H. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aims to determine the thermodynamic properties of damaged beans. Grains with initial moisture content of 53.85% (d.b.) were used. A part of the grains was used to obtain the desorption isotherms, while another part was subjected to drying until a moisture content of 5.26% (d.b.) was achieved; therefore, it was subjected to the adsorption process. To induce damage, a Stein breakage tester was used. To obtain the equilibrium moisture content, grains were placed in a climatic chamber whose temperatures were 20, 30, 40, and 50 ± 1 °C combined with a relative humidity of 30, 40, 50, 70, and 90 ± 3%. Although in the desorption process, damaged grains had a lower differential enthalpy compared with the control, the reverse behavior was observed in the adsorption process. Mechanical damage caused the formation of a greater number of available adsorption sites, resulting in higher differential entropy values in adsorption and lower values in desorption compared with the control. The mechanical damage had no effect on the Gibbs free energy.